The Social World(s) of The Scooter: Two-Wheeled Mobilities in Cairo and Alexandria - El Serougui, Ahmed (AUC Knowledge Fountain, 2022)
My research project looks at the scooter as a particular type of two-wheeled motorcycle, which has shot into prominence as a specific mode of transportation used by middle class women and men in the past few years and has been notably visible in prominent Egyptian cities. This research is based on a multi-sited ethnography in Alexandria and Cairo, tracing the scooter through the urban landscape in time and space, addressing first questions related to navigating the city in times of pandemic and what kind of theory could be produced from these ordinary cities in such an extraordinary time. This research looks at the material trajectories of the scooter by writing a possible social biography of it, reading it in the context of the larger navigational urban grammar of both Cairo and Alexandria: engaging with questions of relationality with other modes of transportation prominent in the Egyptian context, private and public modes of transportation. As it follows, this research looks also into the different figures driving these vehicles, where the “Youthful” character of the scooter’s rider allows a particular narrative and the consolidation of a sub-culture, which builds networks, markets, and a vocabulary both in the material and virtual worlds. The variety of activities around the scooter allows to shed light on the laboring practices around it. These practices have taken different shapes and have been motivated and actualized by an array of formal policies, informal agreements, personal histories, and collective imaginaries in the face of economic and social precarity, accentuated in time of pandemic. The activities surrounding the scooter also extend the gender element in this experience, in an attempt to understand how women navigate the scooter on two-wheels motorcycle, and what kind of gender politics are present when on the move, looking at the different discussions, compromises, maneuvers to see and be seen on the road, and how that then femineity and masculinity is performed on the go. Finally, using both participant observation and autoethnography, this research looks at the body and its rhythms in the city: unpacking the always-present (and even probable) possibility of an accident while riding a scooter as an inherent and organic affective urban presence, and how this mentality of near-miss lends itself to other form of risk-taking, allowing the experience of riding the scooter to be lived as a form of urban play, and as such, reshaping the subject’s affective relationship to the city by having their bodies in & out of rhythms.